A comprehensive structural steelwork computer aided design and datailing system - Chang, Huann-jeng; Brotton, D.M.; Pama, Ricardo P.; Pichai Nimityongskul; (The Retired Serviceman Engineering Agency ) RSEA, Taiwan , R.O.C. (Bangkok : Asian Institute of Technology, 1986)
Following the modification of the original project brief due to uncontrollable circumstances the author has carried out an investigation of t he available hardware and software which could lead to the preparation of a comprehensive structural steelwork computer aided design and detailing system. Four systems were investigated and their scope and potential compared through the carrying out of related example problems. Discussion of the results of the investigation has enabled the author to make both short term and longer term recommendations for future research in this area
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Steel, Structural -- Design and construction; Computer drawing